Arctic Sea, plans in Arctic America / published at the Admiralty (Great Britain. Hydrographic Office, 1912)
New edition 24th July 1912 Relief shown by hachures and spot heights. Depths shown by soundings and bathymetric isolines.; Sheet includes blank space in lower right. Melville Island, Winter Harbour -- North Somerset I., Batty Bay -- Boothia I., Victoria Harbour -- Cockburn I., Port Neill -- Cockburn I., Port Bowen - Boothia I., Elizabeth Harbour -- North Somerset I., Port Leopold -- Grinnel Peninsula, Northumberland Sound. Grayscale